Does model of maternity care make a difference to birth outcomes for young women? A retrospective cohort study. Issue 8 (August 2015) - Allen, Jyai; Gibbons, Kristen; Beckmann, Michael; Tracy, Mark; Stapleton, Helen; Kildea, Sue
Abstract Background Adolescent pregnancy is associated with adverse outcomes including preterm birth, admission to the neonatal intensive care unit, low birth weight infants, and artificial feeding. Objective To determine if caseload midwifery or young women's clinic are associated with improved perinatal outcomes when compared to standard care. Design A retrospective cohort study. Setting A tertiary Australian hospital where routine maternity care is delivered alongside two community-based maternity care models specifically for young women aged 21 years or less: caseload midwifery (known midwife) and young women's clinic (rostered midwife). Participants All pregnant women aged 21 years or less, with a singleton pregnancy, who attended a minimum of two antenatal visits, and who birthed a baby (without congenital abnormality) at the study hospital during May 2008 to December 2012. Methods Caseload midwifery and young women's clinic were each compared to standard maternity care, but not with each other, for four primary outcomes: preterm birth (<37 weeks gestation), low birth weight infants (<2500 g), neonatal intensive care unit admission, and breastfeeding initiation. Two analyses were performed on the primary outcomes to examine potential associations between maternity care type and perinatal outcomes: intention-to-treat (model of care at booking) and treatment-received (model of care on admission for labour/birth). Results 1908 births were analysed by intention-to-treat and treatment-received analyses. Young women allocated to caseload care at booking, compared to standard care, were less likely to have a preterm birth (adjusted odds ratio 0.59 (0.38–0.90, p = 0.014)) or a neonatal intensive care unit admission adjusted odds ratio 0.42 (0.22–0.82, p = 0.010). Rates of low birth weight infants and breastfeeding initiation were similar between caseload and standard care participants. Participants allocated to young women's clinic at booking, compared to standard care, were less likely to have a low birth weight infant adjusted odds ratio 0.49 (0.24–1.00, p = 0.049), however when analysed by treatment-received, this finding was not significant. There was no difference in the other primary outcomes. Conclusions Young women who were allocated to caseload midwifery at booking, and/or were receiving caseload midwifery at the time of admission for birth, were less likely to experience preterm birth and neonatal intensive care unit admission.